Level of reading comprehension in dentistry students of the Metropolitan University, Barranquilla – Colombia (Revista Nacional de Odontología, 2022)
Learning is closely related to oral and written language, this being of vital importance in the development of every human being to communicate correctly, fundamental aspect in every professional.In the educational context the low capacity of the students in the elaboration of written compositions, comprehension and interpretation of texts is observed. That is why it is necessary to strengthen the generic competence called reading comprehension (critical reading).This article aims to determine the current state of reading comprehension level of Dentistry students of the Universidad Metropolitana of Barranquilla (Colombia) by gender and type of educational institution, the representative sample was 188 students from I to X semester.The Instrument to measure Reading Comprehension in University Students (ICLAU) was applied, which is an expository-argumentative text entitled “Evolution and its history”, which presents a narration of 965 words. The text contains 7 items to evaluate five levels of understanding: Literal, Information Reorganization, Inferential, Critical and Appreciative. This instrument has already been validated by Guerra & Guevara (2013).The results obtained show certain shortcomings in students for the comprehension of texts, which invites us to create strategies for the continuous improvement of said competence.
Keywords: reading comprehension; students; dentistry